A hit‐and‐run heat shock factor governs sustained histone methylation and transcriptional stress memory. (9th December 2015) - Lämke, Jörn; Brzezinka, Krzysztof; Altmann, Simone; Bäurle, Isabel
Abstract: In nature, plants often encounter chronic or recurring stressful conditions. Recent results indicate that plants can remember a past exposure to stress to be better prepared for a future stress incident. However, the molecular basis of this is poorly understood. Here, we report the involvement of chromatin modifications in the maintenance of acquired thermotolerance (heat stress [HS] memory). HS memory is associated with the accumulation of histone H3 lysine 4 di‐ and trimethylation at memory‐related loci. This accumulation outlasts their transcriptional activity and marks them as recently transcriptionally active. High accumulation of H3K4 methylation is associated with hyper‐induction of gene expression upon a recurring HS. This transcriptional memory and the sustained accumulation of H3K4 methylation depend on HSFA2, a transcription factor that is required for HS memory, but not initial heat responses. Interestingly, HSFA2 associates with memory‐related loci transiently during the early stages following HS. In summary, we show that transcriptional memory after HS is associated with sustained H3K4 hyper‐methylation and depends on a hit‐and‐run transcription factor, thus providing a molecular framework for HS memory. Synopsis: Stress exposure can prime for an enhanced response upon re‐exposure. In Arabidopsis, heat stress‐mediated priming is associated with stable histone H3 lysine 4 di‐ and trimethylation and requires transcription factor HSFA2 that only transiently binds to the primed gene loci. Heat stress primes genes for sustained activation and/or enhanced induction upon recurring stress. This transcriptional memory is linked to induction of histone H3 lysine 4 di‐ and trimethylation. Transcription factor HSFA2 is required for transcriptional memory. HSFA2 only transiently associates with the gene loci, suggesting it acts in a hit‐and‐run mode. Abstract : Stress exposure can prime for an enhanced response upon re‐exposure. In Arabidopsis, heat stress‐mediated priming is associated with stable histone H3 lysine 4 di‐ and trimethylation and requires transcription factor HSFA2 that only transiently binds to the primed gene loci.